Analysis of the Effect of Vehicle Load on Road Layer Damage on Alluvial Bedrock Using PCI and ESAL Approaches: A Case Study of Air Molek–Taluk Kuantan Road, Riau Province, Indonesia - Ulum, Bustanul; Elizar; Syahminan, Mohammad (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The Molek-Taluk Kuantan Air Road in Indragiri Hulu Regency, Riau, has suffered a lot of damage due to frequent crossings by heavily loaded vehicles. This study aims to find out how much the vehicle load affects the damage to the road, as well as see how soil conditions and the shape of the area contribute to the worsening of the damage. The assessment was carried out using the PCI (Pavement Condition Index) method to see the level of physical damage to the road, and the ESAL (Equivalent Single Axle Load) method to calculate the vehicle load. The observation results show that the number of vehicles passing by reaches more than 4,000 per day, with a high overload rate (Truck Factor = 3.93). In addition, the soil structure in this region consists of soft soils such as clay and peatlands, which are very susceptible to damage if constantly subjected to heavy loads. The area through which the road passes also has a slope that can cause erosion and soil shift. Overall, the average road condition was in the damaged category (PCI value = 37.4). The results of this study show the need to repair roads that take into account soil conditions, strengthening drainage, and limiting vehicle loads so that damage does not continue to recur.